PATTERNS OF RELATIVE GROWTH IN TROPICAL NERITIDS, NERITA UNDATA, BASED ON OPERCULUM ANALYSIS - Uneputty, Prulley A. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
Growth is one of the important events in the life history of an organism beside reproduction. The objective of the present study was to evaluate the possibility of using the operculum to determine the growth pattern of tropical neritids (Nerita undata). Shell and operculum dimension were measured using a vernier caliper to the nearest 0.01mm. The results showed that there was a relationship between operculum dimensions (length and width) and shell, and it was also shown allometric growth pattern. The study also indicated the relationship between operculum dimension and the shell parameters.